Discourses of Truck Container Signs in Indonesia - I Dewa Putu Wijana (Journal of Language and Literature, 2022)
This article attempts to analyze truck container sign discourses found in Indonesia from three perspectives: linguistics, sociolinguistics, and pragmatics. Using data collected from google search and one from my data collection, through careful observation and contextual method, it is found that structurally the truck signs can be constructed in the forms of single sentence discourse and multi-sentence discourse of a maximum of 9 sentences. The language style used is informal or colloquial, characterized by massive code-mixing among three out of four languages, i.e. Indonesian, Javanese, English, and Sundanese. The discourses are exploited to perform various kinds of speech acts in varieties of strategies and to carry out many communicative functions: emotive, conative, referential, phatic, metalingual, poetic, and recreative.